2012
DOI: 10.1088/0256-307x/29/4/046201
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Equation of States of the Solid and Liquid Phases of Al and Ta

Abstract: The multiphase equation of states (EOSs) of both the solid and liquid phases of Al and Ta are presented. These EOSs are carried out on the basis of the Helmholtz free energy, where the ion vibration free energy is evaluated from the mean field potential (MFP) model we recently proposed [Physica B 406 (2011) 4163]. The calculated results show that our multiphase EOSs can give a good reproduction of the measured phase diagrams and other experimental data, including static high-pressure measurements, shock Hugoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…32 The free-surface velocity of the first shock was estimated to be approximately 5.9 km/s, and, accordingly, the shock-breakout pressure was estimated to be approximately 75 GPa, which is slightly higher than the release-melting pressure of 70 GPa. 33 This indicates that the target was in the solid-liquid mixture region of the phase diagram prior to fragmentation, which resulted in the FIG. 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 The free-surface velocity of the first shock was estimated to be approximately 5.9 km/s, and, accordingly, the shock-breakout pressure was estimated to be approximately 75 GPa, which is slightly higher than the release-melting pressure of 70 GPa. 33 This indicates that the target was in the solid-liquid mixture region of the phase diagram prior to fragmentation, which resulted in the FIG. 3.…”
Section: Resultsmentioning
confidence: 99%
“…We estimated the free-surface velocity of the second shock to be approximately 8.6 km/s, representing a shock-breakout pressure of approximately 130 GPa, which is higher than the shock-melting pressure of approximately 120 GPa. 33 Thus, the target was completely liquid prior to fragmentation, which resulted in the target fragmenting into fine liquid droplets. The areal mass density of the fragmentation product was derived using the following method.…”
Section: Resultsmentioning
confidence: 99%
“…The phase transition of Ta metal under high pressure is a hot research topic at present. [1][2][3][4][5][6][7][8][9][10][11][12] Ta is a bcc structure under the standard condition, but the phase transition of the crystal under high pressure and high temperature is very complex, thus it has been extensively studied. Hsiung and Lassila found that Ta transformed from the bcc structure to the hcp structure by the impact test of 45 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a lot of studies on the energy characteristics during the process of material deformation and failure have been done [5][6][7][8][9][10][11][12] . Some scholars tried to establish strength theory of materials based on energy principles, and have made gratifying progress.…”
Section: Introductionmentioning
confidence: 99%